2022
DOI: 10.1038/s41598-022-20186-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal telomerase transcripts reprogram the microRNA transcriptome profile of fibroblasts and partially contribute to CAF formation

Abstract: It is now well accepted that cancer cells change their microenvironment from normal to tumor-supportive state to provide sustained tumor growth, metastasis and drug resistance. These processes are partially carried out by exosomes, nano-sized vesicles secreted from cells, shuttled from donor to recipient cells containing a cargo of nucleic acids, proteins and lipids. By transferring biologically active molecules, cancer-derived exosomes may transform microenvironmental cells to become tumor supportive. Telomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Moreover, the low expression levels in iMSC-EVs closely resembled those observed in primary MSC cells, diminishing concerns over safety. Other studies, contrarily to our results, reported hTERT mRNA to be highly secreted in EVs obtained using other isolation methods, such as ultracentrifugation of cultured human amniocytes conditioned media [41] , and Jurkat cell lines [42] , as well as precipitation-isolated tumor cells-derived EVs [43,44] . Furthermore, the same studies showed a functional effect on target cells mediated by the transfer of EV-associated hTERT mRNA.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the low expression levels in iMSC-EVs closely resembled those observed in primary MSC cells, diminishing concerns over safety. Other studies, contrarily to our results, reported hTERT mRNA to be highly secreted in EVs obtained using other isolation methods, such as ultracentrifugation of cultured human amniocytes conditioned media [41] , and Jurkat cell lines [42] , as well as precipitation-isolated tumor cells-derived EVs [43,44] . Furthermore, the same studies showed a functional effect on target cells mediated by the transfer of EV-associated hTERT mRNA.…”
Section: Discussionsupporting
confidence: 82%
“…Subsequently, these telomerase-positive cells represent a new cell type-nontumor cells with enhanced telomerase activity [119]. A more recent study reported that exosomal telomerase may play a role in modifying normal fibroblasts into cancer-associated fibroblasts by upregulating αSMA and vimentin [68]. As previously mentioned, the interaction of tumor cells with CAFs is mutualistic.…”
Section: Tgf-β1mentioning
confidence: 90%
“…Directly target the oncosuppressor CSRP2, induction of the ERK and PAK/LIMK/cortactin signaling cascades [117,118] hTERT Enhancement of telomerase activity [119] Upregulations of αSMA and vimentin [68] Tumor-associated macrophages (TAMs)…”
Section: Cells Of Tme Tumor Cells Ev Factors Consequence Referencementioning
confidence: 99%
“…Downregulation of Thioredoxin interacting protein (TXNIP) by miR‐146a also activates the Wnt pathway in breast cancer cells which supports invasion and metastasis 75 . TDEs‐encapsulated transcript of human telomerase reverse transcriptase contributes to fibroblast activation through increasing α‐SMA and vimentin expression and also via modulation of fibroblast's microRNA transcriptome profile 76 . Transfer of TDE lncRNA Gm26809 to fibroblasts improved proliferation and invasion of melanoma cells via CAFs 77 .…”
Section: Tde Rna and Activation Of Cafsmentioning
confidence: 99%